2016
DOI: 10.1007/s10334-016-0593-9
|View full text |Cite
|
Sign up to set email alerts
|

Can MRI T1 be used to detect early changes in 5xFAD Alzheimer’s mouse brain?

Abstract: ObjectivesIn the present study, we have tested whether MRI T1 relaxation time is a sensitive marker to detect early stages of amyloidosis and gliosis in the young 5xFAD transgenic mouse, a well-established animal model for Alzheimer’s disease.Materials and methods5xFAD and wild-type mice were imaged in a 4.7 T Varian horizontal bore MRI system to generate T1 quantitative maps using the spin-echo multi-slice sequence. Following immunostaining for glial fibrillary acidic protein, Iba-1, and amyloid-β, T1 and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, the dietary intervention had a significant, moderate mitigating effect on inflammatory expression, as the CR partially reversed neuroinflammation in the old animals. Other studies have also revealed a significant increase in hippocampal inflammation during aging [ 22 , 50 , 70 ], demonstrating that CR might attenuate markers of neuroinflammation and plasma cytokines [ 71 ]. This attenuation of microglial activation might dampen the release of pro-inflammatory cytokines, helping to prevent neural loss and the impairment of cognitive performance during aging [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the dietary intervention had a significant, moderate mitigating effect on inflammatory expression, as the CR partially reversed neuroinflammation in the old animals. Other studies have also revealed a significant increase in hippocampal inflammation during aging [ 22 , 50 , 70 ], demonstrating that CR might attenuate markers of neuroinflammation and plasma cytokines [ 71 ]. This attenuation of microglial activation might dampen the release of pro-inflammatory cytokines, helping to prevent neural loss and the impairment of cognitive performance during aging [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, microglia with a neurotoxic phenotype are considered to participate in the phagocytosis of new-born neurons that fail to integrate into existing circuits, regulating glutamatergic receptor maturation and synaptic transmission, and supporting synaptic pruning [ 21 ]. In line with this, the macrophage/microglial ionized calcium-binding adaptor 1 (Iba-1) marker was significantly elevated in the HPC of aged animals compared to adults [ 22 ].…”
Section: Introductionmentioning
confidence: 91%
“…Spencer and colleagues used multimodal MRI to develop diagnostic markers of AD [ 65 , 73 ]. T1WI and T2WI, alongside histological staining, in 11-month-old 5xFAD mice revealed lower T1 relaxation times (s) in male/female 5xFAD mice.…”
Section: Neuroimaging Of Mouse Models Of Admentioning
confidence: 99%
“…They then tested the hypothesis that T1 relaxation times could be used as a sensitive marker to detect Aβ load at early stages. However, T1 values were not significantly different between WT and 5xFAD at younger ages (2.5- and 5-month-old) prior to the onset of robust Aβ deposition [ 73 ]. At 11 months of age, there were no significant differences between WT and 5xFAD T2 values [ 65 ].…”
Section: Neuroimaging Of Mouse Models Of Admentioning
confidence: 99%